FACTORS AFFECTING THE NON-COMPLETION OF DEGREES UNDER THE COLLEGE OF COLLEGE OF BUSINESS ADMINSTRATION AND ACCOUNTANCY (CBAA), COLLEGE OF EDUCATION (COEd) , COLLEGE OF LIBERAL ARTS AND COMMUNICATION(CLAC), COLLEGE OF SCIENCE AND COMPUTER STUDIES (CSCS) - VALERA, FELINORE ANGELICA; MERCADO, EDNA; SALIBAY, CRISTINA (12th International Scholars Conference 2025, 2026)
This study explores the factors contributing to the non-completion of degree programs among students from four colleges at De La Salle University-Dasmariñas (DLSU-D): the College of Business Administration and Accountancy (CBAA), College of Education (COEd), College of Liberal Arts and Communication (CLAC), and College of Science and Computer Studies (CSCS). Utilizing a structured survey and purposive sampling, data were collected on students’ background, academic history, and reasons for discontinuing their studies. Findings indicate that most non-completers were male, aged 21–22, residing in Cavite, and employed in freelance or BPO sectors. Many had completed 24 or more academic units prior to leaving, with financial constraints and family-related issues cited as the primary causes. The highest dropout rates occurred during the pandemic period. Respondents shared mixed views on their university experience, acknowledging both strengths and areas for improvement. These insights highlight the importance of implementing targeted support systems, flexible financial aid options, and proactive follow-up strategies to reduce student attrition and encourage degree completion.